An optimisation method for urban artery coordinated control based on the cosine modified adaptive genetic algorithm. (2015) - Qi, Lei; Ma, Changxi; He, Ruichun
In order to relieve the traffic congestion, especially the traffic burden of the artery in the urban road network, this paper proposes an arterial traffic coordinated control optimisation method by using the cosine modified adaptive genetic algorithm. Firstly, this paper considers the importance of different directions traffic release of intersections coordinated phase, and takes the number of vehicles within the maximised green wave bandwidth as the objective to establish the traffic coordinated control model. Secondly, the cosine modified adaptive genetic algorithm is applied to solve the model. Finally, the traffic coordinated control system including six consecutive intersections is designed in Tianshui Road, Lanzhou, China. The optimisation result shows that the cosine modified adaptive genetic algorithm has a good performance in the optimisation of the traffic coordinated control system.